Comparison of serum specific IgE with skin prick test in the diagnosis of allergy in Malaysia - Asha'ari, Zamzil Amin; Yusof, Suhaimi; Yusof, Rosnida Azura; Ismail, Rushdan; CYC, Maraina (Malaysian Medical Associations, 2011)
We compared a newer serum specific IgE (SSIgE) test with skin prick testing (SPT) in the diagnosis of allergy in Malaysia. Ninety newly diagnosed allergic patients were enrolled for both tests. Using SPT as a clinical gold standard,the sensitivity, specificity, positive, and negative predictive values (PPV, NPV) were calculated for SSIgE for each of the common allergens tested. The highest positive results for both SPT and SSIgE were for house dust mite and cat. Compared to SPT, SSIgE showed better sensitivity but poorer specificity, low PPV and good NPV in all the allergens tested. Significant positive correlation was seen between the diameter of wheal and flare of SPT and the SSIgE results.